Learning for life, a structured and motivational process of knowledge construction in the acquisition/learning of English as a foreign language in native Spanish speakers - Miño-Garcés, Fernando (International Journal of English Studies, 2009)
As language learning theory has shifted from a highly guided to a more open learning process, this paper presents the teaching/learning philosophy called Learning for Life (L for L) as a great way to motivate native Spanish speaker students learning English as a foreign language, and to help them be the constructors of their own knowledge. The Learning for Life philosophy was created by Patricia López de Jaramillo, M.A. and Fernando Miño-Garcés, Ph.D. at the Andean Center for Latin American Studies (ACLAS) in Quito – Ecuador. In the Learning for Life philosophy, the learner is the center of the process and becomes the creator of his/her own knowledge. To get to this new dimension in learning, acquisition is emphasized, and the principles of this philosophy are applied in the EFL classroom. The definition of the philosophy and its principles are presented, and explained in detail as to how they can be applied in the teaching of a foreign language. This paper also explains the difference between acquisition versus learning, and what process should be applied in the classroom to emphasize on acquisition, and not so much on learning.